PENGARUH PROMSI DAN ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPATU SNEAKERS (Studi pada konsumen Bjo SneakersMind di Kota Malang) - Muhammad Rizky Nopeyandi (Manajemen Bisnis, 2018)
This study aims to examine the effect of promotion and product attributes (consisting of brand, product quality, product features, product design, labels, warranties, and complementary services) to consumers' buying decisions as sneakers Bjo SneakersMind in Malang. Analytical techniques used are multiple linear regression analysis and classical assumption test. From the data collected by using the questionnaire (questionnaire) with the number of samples of 100 respondents. The results show that promotion (through electronic media, print media, and personal sales) and product attributes (consisting of brand, product quality, product features, product design, labels, guarantee and complementary services) have a positive and significant effect on purchasing decisions Sneakers on Bjo SneakersMind consumers.